Superstars without Talent? The Yule Distribution Controversy - Spierdijk, Laura; Voorneveld, Mark (The Review of Economics and Statistics, 2009)
Chung and Cox (1994) provided an intuitively appealing stochastic model indicating that superstars may exist regardless of talent, giving rise to the Yule distribution. We adopt a different empirical approach and test its goodness of fit using a parametric bootstrap and several powerful test statistics. Just like the discrete Pareto distribution, it is overwhelmingly rejected: it is a fairly accurate approximation of the lower quantiles of the superstar distribution but overestimates the snowball effect that makes consumers purchase records of the most successful artists. In other words, the Yule distribution captures stardom, but not superstardom. A generalization of the Yule distribution provides an excellent fit in two of the three data sets.